A case of renal cell carcinoma suspected of multilocular cystic nephroma - Maeda, S (Hinyokika kiyo. Acta urologica Japonica, 1988)
A 52-year-old, healthy looking woman was referred for further evaluation of left renal mass, She had had a history of hematuria for ten years. Admission laboratory studies were within normal limits except for slight elevation of white blood cell count, c-reactive protein, blood sedimentation rate and immunosuppressive acidic protein. Retrograde pyelography demonstrated a large mass with ringed calcification in the middle lobe of the left kidney. The multiloculated mass was also confirmed by computed tomography and ultrasonography. Selective left renal arteriography showed stretched arteries and irregularity and tortuosity of the smaller vessels. Under a presumptive diagnosis of multilocular cystic nephroma or renal cell carcinoma, left radical nephrectomy was performed. In surgical specimen, many lobules were filled with serous fluid and clotted blood. Microscopic examination revealed that the lining of the cyst wall consisted of renal cell carcinoma cell. At present, 5 months after the operation, she is well without any signs or symptoms of recurrence